Cryptic Ontogenetic Changes in the Ventral Coloration of a Color Polymorphic Wall Lizard (Podarcis muralis) - Abalos, Javier ; 0000-0001-9357-7420; Bartolomé, Alicia; de Lanuza, Guillem Pérez i.; Aubret, Fabien; Font, Enrique (Journal of Experimental Zoology Part A: Ecological and Integrative Physiology, 2026)
Many animals undergo irreversible ontogenetic color changes (OCCs), yet these changes are often overlooked despite their potential ethological relevance. The problem is compounded when OCCs involve wavelengths invisible to humans. Wall lizards can perceive ultraviolet (UV) light, and their conspicuous ventral and ventrolateral coloration—including UV-reflecting patched—likely serves social communication. Here, we describe OCCs in the ventral (throat and belly) and ventrolateral (outer ventral scales, OVS) coloration of juvenile common wall lizards (Podarcis muralis) as perceived by conspecifics. We measured reflectance in hatchling and yearling lizards raised under semi-natural conditions and used visual modeling to estimate chromatic distances within individuals and across life stages (i.e., hatchlings, yearlings, and adults). Hatchlings typically exhibit UV-enhanced white (UV+white) on their ventral surfaces (throat, belly, and OVS), a color that is likely discriminable to conspecifics from the most frequent adult colors in the throat (i.e. orange, yellow, and UV-reduced white; UV−white) and OVS (i.e., UV-blue). The prevalence of UV+white decreases with age, with the decline being less pronounced in female bellies. OCCs to UV-blue in the OVS are more apparent in males than in females and appear delayed relative to changes in the throat and belly. While throat colors in yearlings are indistinguishable to conspecifics from adult throat colors, yearling UV-blue patches remain chromatically distinct from those of adults. This delay may reflect variations in the mechanisms of color production or distinct selective pressures acting on these patches. Overall, our results show that OCCs in P. muralis fulfill a key requirement for social signals by being perceptible to conspecifics. This supports the hypothesis that OCCs may play a role mediating interactions between juveniles and adults, as well as delaying the onset of colors involved in social communication.
Keywords: color polymorphism; ontogenetic color changes; Podarcis muralis; sensory ecology; social communication; ultraviolet light perception; visual modeling; wall lizards